HUBUNGAN MOTIVASI TERHADAP KINERJA BIDAN DESA DALAM PELAKSANAAN PROGRAM KELAS IBU HAMIL DI PUSKESMASKABUPATEN PURBALINGGA - Sari, Ossie Happina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The annual report at the Health Office of Purbalingga district increased the number of maternal deaths from 2012 to 21 cases to 22 cases in 2013. Bleeding is the leading cause of maternal death, this is ironic. One attempt to anticipate high maternal mortality, midwives should be equip themselves with adequate skills and knowledge. One of the efforts to improve childbirth in health facilities is by the introduction of maternal class programs. The purpose of this research is to know the influence of motivation on the performance of village midwife in the implementation of KIH. Research Design is an analytic observational with cross sectional approach. The research instrument used a structured questionnaire. Data collection was done by interview. Population in this research is 225 village midwives who work in Purbalingga Purbalingga Health Center area, which has been implementing KIH as many as 165 village midwives. The sampling technique used proportional random sampling with 63 respondents. Bivariate analysis was done by chi square test. good midwife performance with good motivation proportion (81,8%) bigger than motivation not good (36,6%). In poor performance with unfavorable motivation proportion (63,4%) bigger than good motivation (18,2%). Relationship analysis obtained p value = 0,000 means there is a relationship of motivation with the performance of village midwives in implementing maternal class program. Recommended to DKK Purbalingga Guidance and coaching regularly in order to improve the implementation of pregnant women's class. Keywords: Motivation perception, midwife, the pregnant women class